2021
DOI: 10.3346/jkms.2021.36.e162
|View full text |Cite
|
Sign up to set email alerts
|

Modern Health Journalism and the Impact of Social Media

Abstract: Scholarly journals are hubs of hypotheses, evidence-based data, and practice recommendations that shape health research and practice worldwide. The advancement of science and information technologies has made online accessibility a basic requirement, paving the way for the advent of open access publishing, and more recently, to web-based health journalism. Especially in the time of the current pandemic, health professionals have turned to the internet, and primarily to social media, as a source of rapid inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…It has to be noted that patients' preferences should be well recognized because of the variability of social media use regarding age, gender, or education [27]. Furthermore, for quite a while, social media has become a vigorous tool in guiding recognition and credibility in the medical publishing fields [28][29][30]. This has especially accelerated with the pandemic [30].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has to be noted that patients' preferences should be well recognized because of the variability of social media use regarding age, gender, or education [27]. Furthermore, for quite a while, social media has become a vigorous tool in guiding recognition and credibility in the medical publishing fields [28][29][30]. This has especially accelerated with the pandemic [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for quite a while, social media has become a vigorous tool in guiding recognition and credibility in the medical publishing fields [28][29][30]. This has especially accelerated with the pandemic [30]. It has been observed that various social media channels are increasingly used by scholars to comment on articles [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations